COVID-19 and the Maritime and Logistics Sector in Africa - Humphreys, Richard Martin; Dumitrescu, Anca; Biju, Ninan Oommen; Lam, Yin Yin (World Bank, Washington, DC, 2020)
The COVID-19 (coronavirus) pandemic has taken a toll on human life and brought major disruption to economic activity across the world, precipitating an unprecedented global health and economic crisis. Although it is too early for a full assessment of the impact of the pandemic in Africa, it is clear that COVID-19 (coronavirus) has already brought severe hardship, especially to the landlocked and least developed countries, and poor and vulnerable communities. Vulnerable sectors (e.g. tourism, oil and gas industry, maritime, air and road transport, freight forwarding, logistics, and wholesale and retail sectors) have been hard hit and some will not recover. The demand for, and price of many commodities has declined sharply, increasing the vulnerability of many commodity-dependent African countries. The forecast challenges include food insecurity, lack of medical supplies, loss of income and livelihood, difficulties in applying sanitary and physical distancing measures, a looming debt crisis, as well as related political and security risks. The World Bank projected that economic growth will decline to between -2.1 and -5.1 percent in 2020 from 2.4 percent in 2019, leading to the first African recession in 25 years. This short note summarizes the current evidence of the impact on the maritime and logistics sector in African countries and defines a three pillared response for countries to both mitigate the impact of the pandemic and increase the resilience of the sectors going forward. It ends by discussing potential areas of co-operation with the World Bank to those ends.